Evaluasi Arahan Pengembangan Pemukiman Kecamatan IV Angkek dan Kecamatan Canduang Kabupaten Agam Pasca Banjir Bandang - Furqan, Muhammad; Prarikeslan, Widya (TSAQOFAH, 2025)
Sub-district IV Angkek and Sub-district Canduang are areas with complex geographical characteristics. Topographic diversity, the density of the river network, and high rainfall make this area vulnerable to hydrometeorological disasters, especially flash floods. Therefore, it is important to study the suitability of existing settlement land and the direction of settlement development that considers aspects of disaster risk and the physical condition of the region. This research uses a quantitative descriptive method with a Geographic Information System (GIS) approach. The variables analyzed include river density, rainfall, slope, soil type, land use, and disaster vulnerability. Data were obtained through field surveys, satellite image interpretation, and spatial analysis using map overlay, scoring, weighting and risk zoning techniques. This process resulted in a land suitability and risk zoning map that became the basis for settlement spatial decision-making. The results show that areas with optimal suitability for settlement development are in zone S2, which is a green zone with low physical barriers and good accessibility. Most of the central to southern areas are buffer zones that function as transition zones between cultivated areas in the north and limited protected areas in the south. Sustainable management is the key to maximizing the productive potential of the region while maintaining environmental sustainability, especially in the face of high natural disaster risk in both sub-districts.